UML stereotypes for the development of process interaction-driven web applications - Mubin, Siti Azreena; Jantan, Azrul Hazri; Abdullah, Rusli; Kamaruddin, Azrina (Association for Computing Machinery, 2016)
Web applications have been developed rapidly as to support a variety of online processes and transactional workflows involved in the web domain. Although there are several numbers of design modeling concepts existing in web application nowadays, new issues such as interrelated process flow, navigational interaction and graphical user interface still become the biggest attention among researchers. This paper presents UML stereotype extensions, which focus on the process interaction-driven design in the proposed design approach called UEWDM. The uniqueness relies on UML stereotypes usability in the design pattern modeling approach. The new design approach is validated through a case study implementation and verified by web designers. Future works of the design model will be explained and briefly summarized at the end of the paper.